Answer:
Recursive:
![f(1)=35, f(n)=f(n-1)+10](https://tex.z-dn.net/?f=f%281%29%3D35%2C%20f%28n%29%3Df%28n-1%29%2B10)
Explicit:
![f(n)=35+10(n-1)](https://tex.z-dn.net/?f=f%28n%29%3D35%2B10%28n-1%29)
And the 20th term is 225.
Step-by-step explanation:
We have the sequence:
35, 45, 55, 65.
Notice that each subsequent term is 10 more than the previous term.
Therefore, our common difference is (+)10.
Recursive Rule:
The standard format for the recursive rule is:
![f(n)=a, f(n)=f(n-1)+d](https://tex.z-dn.net/?f=f%28n%29%3Da%2C%20f%28n%29%3Df%28n-1%29%2Bd)
Where a is the initial term and d is the common difference.
From our sequence, we know that a the initial term is 35.
And as determined, our common difference d is 10.
Substitute. Hence, our recursive rule is:
![f(1)=35, f(n)=f(n-1)+10](https://tex.z-dn.net/?f=f%281%29%3D35%2C%20f%28n%29%3Df%28n-1%29%2B10)
Explicit Rule:
The standard format for the explicit rule is:
![f(n)=a+d(n-1)](https://tex.z-dn.net/?f=f%28n%29%3Da%2Bd%28n-1%29)
Where a is the initial term and d is the common difference. So, let’s substitute 35 for a and 10 for d. Hence, our explicit formula is:
![f(n)=35+10(n-1)](https://tex.z-dn.net/?f=f%28n%29%3D35%2B10%28n-1%29)
Now, let’s find the 20th term. We will utilize the explicit rule since the recursive rule can get tedious. Substitute 20 for n because we would like to 20th term. Thus:
![f(20)=35+10(20-1)](https://tex.z-dn.net/?f=f%2820%29%3D35%2B10%2820-1%29)
Evaluate:
![\begin{aligned} f(20)&=35+10(19) \\ f(20)&=35+190 \\ f(20)&=225 \end{aligned}](https://tex.z-dn.net/?f=%5Cbegin%7Baligned%7D%20f%2820%29%26%3D35%2B10%2819%29%20%5C%5C%20f%2820%29%26%3D35%2B190%20%5C%5C%20f%2820%29%26%3D225%20%5Cend%7Baligned%7D)
Hence, the 20th term is 225.